CORRECTION OF SPINE DEVIATION IN THE SAGITTAL PLANE - KYPHOSIS THROUGH KINETIC MEANS - Benedek Florian; Raţă Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This paper presents the correction of a physical disability of spine quite common in adolescents. The correction process consists in using kinetic means both on land and in water. The correction period of physical disability of the two patients was three months. In this way the process can be affected by the personality traits specific to each patient.